Clinical researchAltered transcriptional activity of gene encoding GAPDH in peripheral blood mononuclear cells from patients with cardiac syndrome X – an important part in pathology of microvascular angina? - Dabek, Jozefa; Wilczok, Jakub; Kulach, Andrzej; Gasior, Zbigniew (Archives of Medical Science, 2010)
Introduction : Cardiac syndrome X (CSX) is characterized by anginal pain with ECG suggestive of ischaemia and normal coronary arteries at angiography. Pathology of CSX involves microvascular dysfunction and is possibly linked with metabolic syndrome. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is an enzyme involved in glycolysis. The GAPDH gene is a “housekeeping” gene and is used for normalization in quantitative gene expression assays. The aim of the study was to evaluate GAPDH gene expression in CSX. Material and methods : The study was performed in 35 CSX patients and 10 control subjects. mRNA was extracted from peripheral blood mononuclears and the mRNA was assessed by QRT-PCR. Results : GAPDH gene expression was enhanced in CSX patients vs. controls (93022 ±23837 copies/μg vs. 1067 ±240 copies/μg respectively; p < 0.001). Moreover, transcriptional activity of the GAPDH gene was heterogeneous within the CSX group. Conclusions : GAPDH gene expression is markedly enhanced in CSX, which reflects carbohydrate metabolism disturbances and makes the GAPDH gene unsuitable as an endogenous control in patients with CSX.